228 MITRAL VALVE REPAIR WITH RING ANNULOPLASTY: ISCHEMIC VERSUS NONISCHEMIC MITRAL REGURGITATION. (1st January 2006) - Yavrouian, E. J.; Lopez, B.; Moody, M.; Cunningham, M. J.; Starnes, V. A.
Abstract : Background: In the presence of functional mitral regurgitation (MR) it has been established that repair alone by annuloplasty ring insertion is sufficient. This study was conducted to report a single surgeon's experience (V.A.S.) of annuloplasty ring insertion for correction of ischemic versus nonischemic MR. Methods: From 1999 to 2005, 94 patients presented with moderate to severe MR and underwent mitral valve repair (MVRpr) with insertion of an annuloplasty ring. There were 53 males and 41 females (44%) with a mean age of 67 ± 12 years. 54 were classified with ischemic MR. Ischemic MR was defined as (1) a previous myocardial infarction, )2) and/or previous or concomitant coronary artery bypass grafting (CABG), (3) and/or previous stent placement. 40 were classified into the nonischemic MR group. Follow-up information was obtained on 100% of the patients. Results: There were a total of 12 deaths with no operative mortality. 9 deaths occurred in the ischemic MR group and 3 occurred in the nonischemic group. Survival for the ischemic MR group at 1, 3, and 5 years was 89%, 85%, and 73%, respectively. For the nonischemic MR group, survival at 1, 3, and 5 years was 94%, 89%, and 89%, respectively. To assess whether the difference in survival between the ischemic and nonischemic groups is due to the cause of the MR, all baseline characteristics were compared. We tested age, sex, hypertension, diabetes, renal disease, prior TIA or stroke, mean ejection fraction, coronary disease, prior operation, and concurrent CABG. Concurrent CABG and coronary disease were present only in the ischemic group and represented a significant difference between the two groups ( p < .0001). We also found that female sex (p < .001), diabetes (p < .001), a lower ejection fraction (42% or less) (p .025), and prior coronary operations (p < .0001) were present in significantly greater numbers in the ischemic MR group. There was no statistical significance between the groups for postoperative MR (p = .37). Conclusions: Patients undergoing mitral valve repair with annuloplasty ring alone for ischemic MR have a lower survival rate than patients with nonischemic MR. Ischemia, along with confounding medical conditions and patient attributes, contributes to the final outcome in mitral valve repair with ring annuloplasty for ischemic MR. The success of the repair is equivalent between the two groups.